Substrate preferences and redistribution of blue king crab Paralithodes platypus glaucothoe and first crab on natural substrates in the laboratory - Tapella, Federico; Romero, Maria Carolina; Stevens, Bradley G.; Buck, Charles Loren (Journal of Experimental Marine Biology and Ecology)
Despite the importance of blue king crab (BKC) to the Bering Sea fishery, there has been no detailed study of juvenile habitat preferences. Such information is critical for understanding life history and for development of stock enhancement programs. The aims of this study were to determine the natural substrata that glaucothoe prefer to settle on, and whether they or subsequent crab 1 stage (C1) redistribute to different habitats over time. A laboratory experiment was performed in 24 round containers divided in four equal quadrants each filled with one of the following natural substrata: beach sand, gravel, shells and cobble. Containers were assigned to 8 groups of 3 replicates each and were kept at ~ 6-8 °C. Twenty five glaucothoe were released in each container on day 0, and one group of three replicates was removed for examination at each of the following intervals: 24 h, 7, 14, 21, 28, 35, 42 and 49 days. Numbers of swimming and settled specimens on each substrate and period were recorded. Glaucothoe began to settle immediately after being released since no swimming larvae were found during any sampling periods. Substrata complexity was important for the habitat selection and distribution of blue king crab glaucothoe and crab 1 stage. During the glaucothoe stage, beach sand was rejected and cobble, shell and gravel were chosen equally. After glaucothoe molted to crab 1 stage and became bigger, animals preferred cobble and shell instead of gravel and beach sand. Understanding habitat selection is useful not only for management of crab populations, but also for assessing the potential of various habitats for stock enhancement of blue king crabs. Fil: Tapella, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Romero, Maria Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Stevens, Bradley G. Kodiak Fisheries Research Center; Estados Unidos ...